(untitled) (Ibrahim Cardiac Medical Journal, 2019)
Background & objective: Ludwig’s angina (LA) is a potentially life-threatening, rapidly spreading, bilateral cellulitis of the submandibular spaces in children. In the preantibiotic era, the airway obstruction was almost inevitable and case fatality rate was as high as 60%. With the introduction of antibiotics in 1940s the LA has become an uncommon disease. As such, many physicians have limited experience of it. But its early recognition and aggressive management still carries utmost importance to avoid life-threatening acute airway obstruction. Therefore, the present study was undertaken to update the physicians with clinical features and management of Ludwig’s angina. Methods: The present descriptive study was conducted in Bangladesh Institute of Child Health & Dhaka Shisu Hospital, Sher-e-Bangla Nagar, Dhaka between January 2012 to December 2016. Having obtained approval from the Institutional Review Board of the Institute, we retrospectively analyzed the clinical course and management of Ludwig’s angina. During the period a total of 27 patients’ record were found available. Data were collected on demographic and clinical characteristics, causes and predisposing factors, investigations, complications developed and outcome of LA. Penicillin with or without additional anaerobic coverage with clindamycin or metronidazole were used as key patient management strategy. Steroid was given for faster recovery of the patients having airway compromise. Patients who did not recover with conservative treatment underwent surgical treatment with incision and drainage. Result: In the present study children with Ludwig’s angina presented with bilateral swelling of the neck and submandibular region accompanied by pain and induration in the affected region. Systemic symptoms, such as, fever and malaise were also frequently present. Two-thirds (66%) of the children had dehydration and almost half (48%) had toxic look. Over one-third (37%) of the children exhibited, restricted backward and upward elevation of tongue and over half with trismus. Of the systemic signs, high temperature, tachycardia, and tachypnoea were common presentation. One-third of the children exhibited signs of airway obstruction. Fifty percent of the children had the history of toothache (lower molar) one or two weeks prior to the development of Ludwig’s angina, 40% had history of mumps and 3.7% had history of trauma to the mandible. Over one-quarter developed pneumonia with mediastinitis. Airway obstruction, manifested as unable to swallow saliva, dyspnoea, stridor and cyanosis, was exhibited by over 55% of the children and received intravenous steroid for faster recovery from the condition. More than three-quarters (77.7%) of the patients responded to Penicillin with or without clindamycin or metronidazole and those who did not respond to it (22.3%) underwent operative treatment. Conclusion: Despite modern medical and surgical interventions have improved the outcomes of Ludwig’s angina to a great extent, it still remains a potentially lethal disease in the pediatric population. Early recognition of the disease with identification of airway obstruction and prompt intravenous antibiotic therapy could resolve the disease without any complications or need for surgical intervention. Ibrahim Card Med J 2017; 7 (1&2): 51-56